GAMBARAN PENGETAHUAN WANITA USIA SUBUR TENTANG MENOPAUSE DINI (Jurnal Keperawatan Indonesia Florence Nightingale, 2022)
ABSTRACT humans who experience various processes of growth and gradual development during their lives, including the development of reproductive functions. Fertile Age Women (WUS) are women whose reproductive organs function well between the ages of 20 and 45 years. Early menopause is a menopause that comes earlier than menopause in general. Based on observations, knowledge is divided into three categories of levels: good if 76%, sufficient if 56% -75%, and less if ≤ 55%. The level of anxiety of women of childbearing age in dealing with premenopausal age has a severe anxiety of 12 respondents (15.59%). The purpose of this study is to know the description of knowledge of women of childbearing age about early menopause. The method used is a systematic literature review. Secondary data collection techniques with five research journals obtained through Google Scholar. Literature Review results from the five research journals show a description of knowledge of women of childbearing age about early menopause with sufficient knowledge, in journal 1 (60%), journal 2 (55.3%), journal 3 (74%), journal 4 (29%), and journals 5 (67.5%) and (65%). It can be concluded that the description of knowledge of women of childbearing age about early menopause is categorized as having sufficient knowledge, this is influenced by age, education, and information. Recommendations for health service institutions for public health center nurses implementing the MCH program are expected to be effective in promoting promotion. One way is to do counseling about early menopause or provide direct health promotion to women of childbearing age. Key words : Early menopause, Knowledge, Women of childbearing age